PENGARUH PENGALAMAN KERJA, KOMPETENSI, INDEPENDENSI, AKUNTABILITAS, PROFESIONALISME DAN KOMPLEKSITAS TUGAS AUDITOR TERHADAP KUALITAS AUDIT (Studi Empiris Pada KAP Surakarta dan Jogjakarta) - Mulyadi . (STIE AUB Surakarta, 2013)
This study aims to identify and provide empirical evidence that the Work Experience, competence, independence, accountability, professionalism and Auditor Task Complexity significant effect on audit quality. Research is a research survey on the public accounting firm in the city of Surakarta and Yogyakarta city. The population in this study are all members of the colleagues who work in public accounting firm in the public accounting firm in the city of Surakarta and Yogyakarta city. This research used samples with a sampling technique that is proportional random sampling. Study population with 66 members and associates a sample of 50 members who are also co-respondents. Data analysis was performed with 1) an analysis of the research instruments which include the validity and reliability testing, 2) analysis of the classical assumptions, 3) linear regression, 4) test the hypothesis that includes the t test, F test and the coefficient of determination (R2).That the results obtained by analysis of F test result are variable Work Experience, Competence, Independence, Accountability, and Professionalism Task Complexity Auditor together affect audit quality. While the t test results showed each variable Work Experience, Competence, Independence, Accountability, and Professionalism Task Complexity Auditor significantly affect audit quality. Results of calculation of the coefficient of determination shows the influence of the independent variables are given in the form of variable competence, independence, accountability, professionalism, and the complexity of the Auditor for audit quality in the public accounting firm of Surakarta and Yogyakarta at 85.7%, while the remaining 16.3% is influenced by other variables not been examined outside the model. Keywords: Work Experience, Competence, Independence, Accountability, Professionalism, Task Complexity and the quality result of audit